2016
DOI: 10.1021/acssuschemeng.5b01669
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted, Metal-Free, Base-Mediated C–N Bond Formation/Cleavage: Synthesis of Benzimidazo[1,2-a]quinazoline Derivatives

Abstract: A novel, rapid, and efficient microwave-assisted, metal-free, base-mediated approach has been developed for the construction of benzimidazo­[1,2-a]­quinazolines from readily available building blocks. This synthetic strategy affords a diverse range of benzimidazo­[1,2-a]­quinazoline derivatives in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…9,13,14 Wang and Singh reported that N -(2-benzimidazoyl)-2-aminobenzamides react with 2-bromobenzaldehydes in the presence or absence of CuI and l -proline to afford benzo[4,5]imidazo[1,2- a ]quinazolines via Ullmann-type C–N coupling followed by double C–N bond cleavage. 13 Such a similar C–N coupling for eventual formation of benzo[4,5]imidazo[1,2- a ]quinazoline was also exemplified by copper-catalyzed reaction between 2-bromobenzoic acid and 2-aminobenzimidazole. 14 However, to the best of our knowledge, no reports are found for the biological activities of such scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…9,13,14 Wang and Singh reported that N -(2-benzimidazoyl)-2-aminobenzamides react with 2-bromobenzaldehydes in the presence or absence of CuI and l -proline to afford benzo[4,5]imidazo[1,2- a ]quinazolines via Ullmann-type C–N coupling followed by double C–N bond cleavage. 13 Such a similar C–N coupling for eventual formation of benzo[4,5]imidazo[1,2- a ]quinazoline was also exemplified by copper-catalyzed reaction between 2-bromobenzoic acid and 2-aminobenzimidazole. 14 However, to the best of our knowledge, no reports are found for the biological activities of such scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Henceforth, aldehydes were employed as starting materials in important organic reactions such as addition, condensation, hydrogenation, coupling, etc. [26][27][28][29][30][31] Over the course of time, aldehydes were also employed in radical acylation and oxidative acylation reactions that result in the direct regioselective formation of new C-C and C-N bonds. These routes provided better alternatives to anhydrides, acyl halides, -ketoacids and other acylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conductive heating, the thermal mechanisms of rate acceleration are the superheating effect of solvents; the formation of so-called molecular radiators; the selective heating by using a strongly absorbing microwave catalyst or reagent in a less polar reaction medium; and the elimination of wall effects found in convective heating. A large number of green and sustainable approaches towards microwave-assisted organic synthesis (MAOS) have been reported, showing different advantages when compared with conventional heating protocols [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Microwave technology could also allow reactions at temperatures up to 300 °C and pressures up to 80 bar with safety priority and excellent parameter controls.…”
Section: Introductionmentioning
confidence: 99%